POLA BAKTERI PADA ULKUS PENDERITA DIABETES MELITUS DAN UJI KEPEKAAN TERHADAP ANTIBIOTIK CEFTRIAXONE DAN COTRIMOXAZOLE DI RUMAH SAKIT MURNI TEGUH MEDAN - DWINDA RAHMATUN AZHARI PINEM; ANCE ROSLINA (JURNAL ILMIAH SIMANTEK, 2020)
Ulcers are a chronic complication of diabetes mellitus with a risk of ulcers as much as 12-25%. Antibiotics are used to treatexisting ulcers, but already resistance to antibiotic broad spectrum of penicillin and cephalosporin. An antibiotic sensitivitytest is carried out to choose which one to use according to the causative bacteria, to cut down the cost of drugs,hospitalization days, and the incidence of amputation. This study is an observasional descriptive study using a crosssectionaldesign by taking ulcer swab in DM patients in Murni Teguh Hospital Medan. The results of the study were obtainedfrom 22 samples identified as gram-negative bacteria were 72,8% and gram-positive bacteria which was 27,2). The twolargest bacteria were Klebsiella sp (31,8%) and Staphylococcus aureus (27,2%). All samples were resistant to ceftriaxoneand cotrimoxazole antibiotics. The most identified bacteria in the ulcer of patients with DM are Gram-negative bacteria withthe type Klebsiella sp and have been resistant to ceftriaxone and cotrimoxazole antibiotics.